Plagues and diseases through newspapers' reports during the seventeenth century - Georgakakis, Panagiotis (Mos Historicus: A Critical Review of European History, 2023)
Plagues and the transmission of diseases constituted one of the major concerns of people during the early modern period. Although there was a consistent effort from the sixteenth century onwards to find proper solutions to relieve the European citizens, the lack of medical knowledge forced these states to focus mostly on the containment of these diseases and not on finding a cure. Thus, the European states used any available resource in this battle against plagues. One of the most prominent allies in this effort to control the outbreak of diseases was the press. Brochures and pamphlets issued by the authorities, reporting the established policies on plagues, circulated in large numbers during the sixteenth century. The emergence of the newspaper in the early seventeenth century increased this circulation. The purpose of this article is to present the role of Francophone newspapers in propagating public health measures through the relevant reports and advertisements on their issues, during a period when the need for medicines increased, the services provided by apothecaries became necessary for the function of the health system and doctors’ involvement was of upmost importance.